A Photochemical Route to Benzo[a]carbazoles via Domino Elimination/Electrocyclization of 2‐Aryl‐3‐(1‐tosylalkyl)indoles. Issue 4 (22nd February 2013) - Protti, Stefano; Palmieri, Alessandro; Petrini, Marino; Fagnoni, Maurizio; Ballini, Roberto; Albini, Angelo
Abstract The photochemical synthesis of benzo[a]carbazoles from easily synthesizable 2‐aryl‐3‐(1‐tosylalkyl)indoles is presented. Irradiation of these substrates in polar aprotic solvents (acetone or THF) gives selectively the target products in satisfactory yields. This versatile and efficient procedure promises to be a useful alternative to the multistep strategies reported in the literature.